Perancangan Library Trolley Ergonomis Berdasarkan Antropometri Tubuh Manusia - Azriadi, Emon; Kumalasari, Resy; Fitri, Sri Naldi (Journal of Engineering Science and Technology Management, 2022)
Research confirms the importance of anthropometry in ergonomic based product design (Wignjosoebroto, 2000). However, a mismatch between facilities and humans as users still occurs. This results in risks to worker safety and disruption in the work process. Pahlawan Tuanku Tambusai University is one of the campuses in Kampar Riau. The campus has a library which is equipped with various facilities, one of which is a trolley. The trolley functions to move books neatly in large quantities. However, employees experience complaints such as back and wrist pain when using this trolley, which can have a negative impact on their health. Therefore, researchers designed a Library Trolley based on the user's anthropometry. This design is equipped with stairs to make it easier to arrange books on high shelves. The size of the Library Trolley is determined based on percentile calculations of body dimensions. The research results show that Standing Shoulder Height (TBB) uses the 50th percentile, namely 133.9 cm. Shoulder Width (LB) using the 90th percentile is 44.547 cm. The 50th percentile for Standing Elbow Height (TSB) is 101 cm. The 10th percentile for Open Palm Width (LTTB) is 16.3 cm, while Fist Height (TKT) uses the 50th percentile, which is 70.32 cm, and Standing Hand Reach Height (TJTB) uses the 10th percentile, namely 207.174 cm.